2021
DOI: 10.3390/molecules26133900
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Promising Antiviral Agents against SARS-CoV-2 Infection: A Mechanistic Review

Abstract: A newly diagnosed coronavirus in 2019 (COVID-19) has affected all human activities since its discovery. Flavonoids commonly found in the human diet have attracted a lot of attention due to their remarkable biological activities. This paper provides a comprehensive review of the benefits of flavonoids in COVID-19 disease. Previously-reported effects of flavonoids on five RNA viruses with similar clinical manifestations and/or pharmacological treatments, including influenza, human immunodeficiency virus (HIV), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 166 publications
(157 reference statements)
0
34
0
Order By: Relevance
“…153 This effect was mediated through inhibition of endolysosomal TPCs, a pathway involves in the infectivity of SARS-CoV-2, Ebola, and MERS via facilitating viral entry. 153,154 These findings suggest a possible use of naringenin against COVID-19 by targeting TPCs and the Akt/mTOR signaling pathway. 153,[155][156][157] Based on existing knowledge, efforts directed toward designing anti-COVID-19 drugs are focused on impeding virus entry into host cells, inhibiting virus-host protein interactions, and interrupting viral replication, with the aim of aborting the inflammatory responses induced by viral invasion.…”
Section: Antiviral Significance Of Naringeninmentioning
confidence: 90%
“…153 This effect was mediated through inhibition of endolysosomal TPCs, a pathway involves in the infectivity of SARS-CoV-2, Ebola, and MERS via facilitating viral entry. 153,154 These findings suggest a possible use of naringenin against COVID-19 by targeting TPCs and the Akt/mTOR signaling pathway. 153,[155][156][157] Based on existing knowledge, efforts directed toward designing anti-COVID-19 drugs are focused on impeding virus entry into host cells, inhibiting virus-host protein interactions, and interrupting viral replication, with the aim of aborting the inflammatory responses induced by viral invasion.…”
Section: Antiviral Significance Of Naringeninmentioning
confidence: 90%
“…Polyphenols possess a wide range of health benefits and biological activities, including antioxidant [50], antitumoral [51], anti-inflammatory [52], and antiviral properties [53], the latter of which suggests that polyphenols may be useful in the battle against multiple viruses, even SARS-CoV-2 [27,[54][55][56][57][58][59][60][61][62]. In fact, numerous studies have shown that polyphenols exhibit antiviral effects by inhibiting DNA/RNA synthesis [63][64][65][66][67]. Our previous study also demonstrated that miquelianin, a flavonol glucuronide, can compete for the binding site of dATP on HIV-1 reverse transcriptase, inhibiting the viral DNA synthesis by interacting with the last nucleotide of the RNA chain and the binding residues of DNA polymerase [68].…”
Section: Discussionmentioning
confidence: 99%
“…Research related to the management of the disease has culminated in a record number of publications, including a significant amount of work investigating natural compounds in the context of COVID-19. To date, relevant secondary (review) studies have focused either on natural products with known antiviral properties associated with other viral infections (in the sense that some of these properties may render them effective against COVID-19) ( Dejani et al, 2021 ; Ebob et al, 2021 ) or were not focused on single classes of compounds ( da Silva, 2021 ; Ghidoli et al, 2021 ; Khazeei Tabari et al, 2021 ; Kowalczyk et al, 2021 ; Montenegro-Landivar et al, 2021 ) or elaborated on synthetic antiviral regimens ( Shah et al, 2021 ). To the authors best knowledge, a review summarizing the evidence about natural products of different classes on COVID-19 has not been published so far.…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 99%